Platelet Parameters in Nonthrombocytopenic Preeclampsia: A Case-Control Study - Ahmed Jasim Alhusaynei; Hanan Dhannoon Nayyef (مجلة كلية الطب, 2024)
Background: Preeclampsia is a pregnancy-specific, multisystem condition characterized by the onset of de novo hypertension and proteinuria occurring in previously normotensive women after the twentieth week of pregnancy. Pregnancy is associated with a physiological adaptation that leads to changes in the hematological system including platelet parameters.